Development of Assessment for Learning-Based Student Activity Sheets to Enhance Students’ Problem-Solving Skills on Buffer Solution Topics - Azhilah Nasywa Ceria Putrisigit; Muchlis (Postgraduate, University of Mataram, 2026)
Problem-solving skills are important skills that need to be developed in chemistry learning, especially in buffer materials that are abstract and complex. However, the results of preliminary studies show that students' problem-solving skills are still relatively lacking. This research aims to develop Student Activity Sheets (LKS) with an Assessment for Learning (AfL) approach on valid, practical, and effective buffer solution materials to practice problem-solving skills. This research uses the Research and Development (R&D) method with a 4-D model which is modified into a 3-D model, limited to the define, design, and develop stages. The limited trial was carried out on 27 phase F students of SMA Hang Tuah 1 Surabaya using a one-group pretest-posttest design. The results showed that LKS obtained an average validity score of 4.27 with a valid category. The practicality of the LKS is shown by the percentage of student responses of 90.75% and student activities of 87.15%, both in the category of very practical. The effectiveness of the LKS was shown by the percentage of problem-solving skills of 93.29% and the results of the Wilcoxon test (p = 0.000 < 0.05). Thus, this LKS with an AfL approach is declared valid, practical, and effective to train students' problem-solving skills.